2020
DOI: 10.3390/ijerph17010344
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Internal and External Load in School Football According to Gender and Teaching Methodology

Abstract: The design of teaching tasks determines the physical and physiological demands that students are exposed to in physical education classes. The purpose of this study is to quantify and compare, according to gender and teaching methodology, the external (eTL) and internal (iTL) load resulting from the application of two programs that follow different teaching methodologies, i.e., a Tactical Games Approach (TGA) and Direct Instruction (DI), to teach school football. The Ratings of Perceived Exertion (RPEs) record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 49 publications
5
39
0
8
Order By: Relevance
“…Equally, in the analysis of the physical demands involved with the implementation of these programmes and their relation with the learning acquired by the students, it was found that the TGA methodology produced better results in the variables of an external and an internal load than the DI methodology, which permits a greater development of physical fitness in the students and better performance indicators in the game [14]. García-Ceberino et al [15] also indicated that the TGA method favors the physical fitness of students. These results led to the recommendation that physical education teachers use a TGA method for teaching invasion sports in physical education classes [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equally, in the analysis of the physical demands involved with the implementation of these programmes and their relation with the learning acquired by the students, it was found that the TGA methodology produced better results in the variables of an external and an internal load than the DI methodology, which permits a greater development of physical fitness in the students and better performance indicators in the game [14]. García-Ceberino et al [15] also indicated that the TGA method favors the physical fitness of students. These results led to the recommendation that physical education teachers use a TGA method for teaching invasion sports in physical education classes [53].…”
Section: Discussionmentioning
confidence: 99%
“…The pre-test and post-test assessments lasted 55 minutes each, and each time, the principal investigator explained the TCTOF, so that it was completely clear how it had to be filled out. Figure 1, which was designed by García-Ceberino et al [15], summarizes the structure of the TGAS and DIS intervention programmes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater perceived competence is associated to a higher students' intention to be physically active [45], so that the SCAs promote a healthy lifestyle [46]. In addition, these teaching approaches can contribute to the greater physical conditioning of students [7,8].…”
Section: Within-group Differencesmentioning
confidence: 99%
“…In this method, the instructor guides the learners through tactical challenges, including through the use of interrogative feedback [5]. In physical education classes, the use of SCAs for the learning experience is considered to be more beneficial for learners because it allows for greater involvement in the decision-making process, has the potential to generate a deeper understanding of the game [2,6], and can potentially contribute to the physical conditioning of the learners, if appropriately designed [7,8].…”
Section: Introductionmentioning
confidence: 99%